European Portuguese Phonetics: Difficulties for Chinese Speakers - Considerations - Nunes, Ana Margarida (JOURNAL OF ADVANCES IN LINGUISTICS, 2014)
The present paper is a pilot study focusing the common difficulties that either Mandarin or Cantonese speakers present on writing Portuguese. The observed problems are an obstacle on the accurate learning of European Portuguese and are related with the Portuguese minimal pairs [p]/[b]; [t]/[d]; [k]/[g] that are often misunderstood. Those specific examples the use of [p] instead of [b] may create a new word but also a different meaning, as example: (small boat) instead of (big vase), or (not existing) instead of (receive). Works of 25 students were selected and 43 occurrences analyzed. Recognizing the limitations of the present research the results show that the prevalent confusion is with the pair [t]/[d] when in CCV context. The study (although recognizing its limitation) should be seen as approaches and reflections that must be deeply studied and data being important to Second Language Teachers and researchers.